Efficacy and safety of bazedoxifene in postmenopausal Latino women with osteoporosis. Issue 9 (September 2017) - Bueno, Jose A. Hernández; Arias, Lizbeth; Yu, Ching-Ray; Williams, Robert; Komm, Barry S.
Abstract: Objective: Bazedoxifene (BZA) reduces fractures and bone turnover in postmenopausal women with osteoporosis. This report evaluates safety and efficacy of BZA in Latin American women in the global trial. Methods: In the 3-year, phase 3, randomized, double-blind trial, postmenopausal women with osteoporosis (N = 7, 492) received BZA 20 or 40 mg/d, raloxifene 60 mg/d, or placebo. Outcomes included vertebral fractures, bone mineral density, bone turnover markers, and safety. This post hoc analysis included 3, 036 Latin American women. Results: Incidence of vertebral fractures at month 36 with BZA 20 mg, BZA 40 mg, raloxifene, and placebo was 1.87%, 1.90%, 1.43%, and 2.83%, respectively (differences not significant). Adjusted mean percentage increases in bone mineral density were 2.49%, 2.79%, 3.18%, and 1.26% for lumbar spine, and 0.40%, 0.95%, 1.11%, and −0.41% for total hip ( P  < 0.001 for BZA 20/40 mg vs placebo). Adjusted median percentage reductions in osteocalcin at month 12 were −43.0%, −44.1%, −46.9%, and −27.0%, and C-telopeptide were −50.7%, −53.4%, −57.6%, and −32.1% ( P  < 0.001 for BZA 20/40 mg vs placebo). Common adverse events included pain and flu syndrome. Conclusions: BZA significantly improved bone mineral density and reduced bone turnover, and numerically reduced fractures, compared with placebo in postmenopausal Latin American women with osteoporosis. Results were similar to the global trial. Abstract : Supplemental Digital Content is available in the text